PERMASALAHAN PEMBELAJARAN MEMBACA CHUUKYUU DOKKAI DI PERGURUAN TINGGI - Sri Wahyu Istana Trahutami (Diponegoro University, 2017)
Reading is a complex process that make teaching dokkai complex too. Dokkai learning problems such as reading activities turned into translating activities, focus on the introduction of kanji and vocabulary, etc.Its necessary to appropriate strategies and methods for teaching chukyuu dokkai.